1988
DOI: 10.1002/syn.890020205
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomer (+)physostigmine prevents organophosphate‐induced subjunctional damage at the neuromuscular synapse by a mechanism not related to cholinesterase carbamylation

Abstract: The natural alkaloid (-)PHY is a reversible anticholinesterase carbamate, but in contrast, its optical isomer (+)PHY, is a very weak anticholinesterase. We have shown that treatment of rats with atropine and (-)PHY prior to injections of a lethal dose of the irreversible organophosphate sarin (0.13 mg/kg) not only protected 100% of the animals from lethality but also reduced the size of the subneural lesions of the nicotinic synapses of skeletal muscle. Similar protection against lethality is provided by pretr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Accordingly, among the carbamaten (+) and (-) physostigmine provided the best protection to animals exposed to lethal doses of OP compounds Kawabuchi et aL, 1988. In vitro experiments carried out for light microsopic and ugtrastructural analyses confirmed these findings.…”
Section: Iv) Carbamates Have Distinct Antidotal Potencies and Selectisupporting
confidence: 68%
See 4 more Smart Citations
“…Accordingly, among the carbamaten (+) and (-) physostigmine provided the best protection to animals exposed to lethal doses of OP compounds Kawabuchi et aL, 1988. In vitro experiments carried out for light microsopic and ugtrastructural analyses confirmed these findings.…”
Section: Iv) Carbamates Have Distinct Antidotal Potencies and Selectisupporting
confidence: 68%
“…Furthermore, these interactions were implicated in the ability of certain carbamates to protect against organophasphate (OP) compounds. Our studies demonstrated that carbamates (Albuquerque et al, , 1988aKawabuchi et aL, 1988Kawabuchi et aL, . 1989) and oximes (Alkondon et al, 1988), chemicals used as antidotes for OP intoxication, alter AChR function by mechanisms not related to AChE inhibition or reactivation.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations